2014
DOI: 10.1007/s00253-014-5849-6
|View full text |Cite
|
Sign up to set email alerts
|

Copper tolerance in Frankia sp. strain EuI1c involves surface binding and copper transport

Abstract: Several Frankia strains have been shown to be copper-tolerant. The mechanism of their copper tolerance was investigated for Frankia sp. strain EuI1c. Copper binding was shown by binding studies. Unusual globular structures were observed on the surface of the bacterium. These globular structures were composed of aggregates containing many relatively smaller "leaf-like" structures. Scanning electron microscopy with energy-dispersive X-ray (SEM-EDAX) analysis of these structures indicated elevated copper and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 70 publications
3
15
0
Order By: Relevance
“…The present study showed that both the metal resistance genes were induced to various extents depending on metal concentration and time of exposure. Previous studies on different metal resistant bacterial strains have shown that genetic determinants for metal transporters belonging to RND family as well as Cu sequestration are induced in presence of elevated levels of heavy metal substrates [10,16,17,29,31,32]. Elevated expression of both copA and czcA genes in response to either of the test metals corroborated very well with a study on transcriptional network involved in metal homeostasis in metal resistant bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…The present study showed that both the metal resistance genes were induced to various extents depending on metal concentration and time of exposure. Previous studies on different metal resistant bacterial strains have shown that genetic determinants for metal transporters belonging to RND family as well as Cu sequestration are induced in presence of elevated levels of heavy metal substrates [10,16,17,29,31,32]. Elevated expression of both copA and czcA genes in response to either of the test metals corroborated very well with a study on transcriptional network involved in metal homeostasis in metal resistant bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…These smaller structures were about 5 μm in diameter and were also observed as individual structures throughout the hyphae. At higher magnification, the structures have a grooved pattern and appear connected to the hyphae by amorphous material [21]. Similar globular structures were observed with SEM of other copper-resistant Frankia strains (e.g., strain DC12).…”
Section: Copper Bioremediationsupporting
confidence: 75%
“…The cells grown in the elevated copper levels appeared blue which suggest that copper was accumulating inside of Frankia or binding to the cell surface [21]. When observed under phase-contrast microscopy, Cu +2 -resistant Frankia EuI1c formed unusual globular structures that were associated with their hyphae [20].…”
Section: Copper Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest neighbor does not necessarily indicate the taxonomy of the query genome but indicates similarity in assigned functions between the query genome and the closest neighbor. cellular mechanisms for increased copper tolerance [41]. The closest neighbor of bin 47, Caulobacter sp.…”
Section: Resultsmentioning
confidence: 99%